Kajian Faktor threat dan coping terhadap Partisipasi Wanita dalam Program Skrining Kanker Leher Rahim - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
In developing countries including Indonesia, 80-90 percent cancer patients usually can not be cured because it is already in late stadium. If it was found in early stadium, more than half of it could be prevented, or even can be cured. Screening program of cervical cancer with pap smear test is one of prevention of cancer which aimed to decrease the mortality rate caused by cancer. Therefore, active participation of women is expected as the threat of cervical cancer considered as number one of types of cancer that affected women. In fact, pap smear test is not yet becoming need that causing low participation of women of women in the screening program of cervical cancer. The goals was to appraise the assoociation between threat and coping factors with women participation in the screening program of cervical cancer in the Bureau of Cancer Consultation Kucala Foundation Yogyakarta. This is an observational research with case control study design. The subjects of this research were women who did pap smear test (screening) for the first time ini Kucala Foundation during the of October 2003 to the 10th of January 2004 that were considered as cases and their neighbor considered as controls. The subjects consisted of 68 cases and 68 controls (1:1). The examined dependent variable was women participation in the screening of cervical cancer. Independent variables were intrinsic rewards, extrinsic rewards, perception of severity, perception of vulnerability, response efficacy, self efficacy and response cost. Data was analyzed in univariat, stratification and multivariat methods. The result showed that all independent variables had significant relationship (P